2014
DOI: 10.1007/s40268-014-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacokinetic Drug Interactions Between Gemigliptin (Dipeptidylpeptidase-4 Inhibitor) and Glimepiride (Sulfonylurea) in Healthy Volunteers

Abstract: PurposeGemigliptin is approved for the treatment of type II diabetes mellitus. Sulfonylureas are commonly used in combination with other antidiabetic drugs to improve glycemic control. The objective of this study was to evaluate the pharmacokinetics, safety, and tolerability of gemigliptin and glimepiride combination therapy compared with those of monotherapies.MethodsA randomized, open-label, crossover study was performed on healthy Korean male volunteers. Each subject received the following treatments (A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…these results were similar to those of studies that evaluated PK interactions between glimepiride and other DPP-4 inhibitors including teneligliptin and gemigliptin. 20,21 Evogliptin is mainly metabolized by CYP3A, whereas glimepiride might be a potential CYP3A4 inhibitor as evinced from the increased plasma concentration of sildenafil that is mainly metabolized by CYP3A4 in rats. 8,22 Additionally, evogliptin did not significantly change the PK properties of glimepiride that is mainly metabolized by CYP2C9, ie, evogliptin did not induce or inhibit CYP enzymes (unpublished in-house data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…these results were similar to those of studies that evaluated PK interactions between glimepiride and other DPP-4 inhibitors including teneligliptin and gemigliptin. 20,21 Evogliptin is mainly metabolized by CYP3A, whereas glimepiride might be a potential CYP3A4 inhibitor as evinced from the increased plasma concentration of sildenafil that is mainly metabolized by CYP3A4 in rats. 8,22 Additionally, evogliptin did not significantly change the PK properties of glimepiride that is mainly metabolized by CYP2C9, ie, evogliptin did not induce or inhibit CYP enzymes (unpublished in-house data).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these results were similar to those of studies that evaluated PK interactions between glimepiride and other DPP-4 inhibitors including teneligliptin and gemigliptin. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Studies also revealed that gemigliptin did not alter the pharmacokinetics of most commonly used antidiabetic agents (metformin, glimepiride, and pioglitazone), antihypertensives, and lipid lowering agents. [ 18 19 20 21 ] Ketoconazole, a CYP3A4 inhibitor, moderately increased gemigliptin exposure while it was reduced when coadministered with rifampicin, a CYP3A4 inducer. [ 22 ]…”
Section: P Harmacokinetics D Osage mentioning
confidence: 99%
“…In several drug-drug interaction studies, gemigliptin did not meaningfully alter pharmacokinetics of co-medications frequently used to treat T2DM, such as antidiabetic agents (metformin, pioglitazone, and glimepiride), and antihypertensive and lipid-lowering agents (irbesartan and rosuvastatin) [ 30 31 32 33 ]. Although co-administration of ketoconazole, a potent inhibitors of CYP3A4, resulted in a moderate increase in gemigliptin exposure (1.9-fold as total active moiety of gemigliptin), no dosage adjustment should be required when gemigliptin is co-administered with ketoconazole.…”
Section: Characteristics Of Gemigliptinmentioning
confidence: 99%